Trajectories of Delinquency and Problem Behavior: Comparison of Social and Personal Control Characteristics of Adjudicated Boys on Synchronous and Nonsynchronous Paths - Le Blanc, Marcel (Journal of quantitative criminology, 1998)
In this paper we identify and distinguish two categories of manifestations of deviance, problem behavior and delinquency, and show that they often follow synchronous developmental sequences. Using data from a sample of 506 adjudicated boys, we investigate the difference between those with synchronous trajectories, in which problem behavior and delinquency follow similar developmental paths, and those with nonsynchronous trajectories, in which the two follow different developmental paths. Comparison of the trajectories shows that personal control variables, such as social maladjustment, value orientation, manifest aggression, and extroversion, are more effective in discriminating between trajectories than are social control variables from school, peer, routine activities, and belief categories. These personal control variables are often not included in studies of delinquency.